The Perceptions of Secondary School Students About Learning Activities from Home Affect Cognitive Learning Outcome in Natural Science Subject - Ariningtyas, Widya; Sartika, Septi Budi; Efendi, Nur (Indonesian Journal of Science Learning (IJSL), 2022)
Study aims to describe students’ perceptions of learning activities from home that affect cognitive learning outcomes in natural science subjects in secondary school school. The research method used is quantitative ex post-facto correlation. The population and sample used were 8th grade students at SMP Muhammadiyah 9 Boarding School Tanggulangin Sidoarjo. Data collection techniques using questionnaires and documents. The data analysis technique used is descriptive qualitative statistics with percentages and inferential statistics with product moment correlation test. The results of research on students’ perceptions of learning activities from home obtained nine indicators, including 1) the effectiveness of learning from home was 72.2% in the fairly good category, 2) access to learning activities from home was 71.6% in the fairly good category, 3) assistance with learning from home at 70.6% in a fairly good category, 4) reactions to learning tasks from home at 48.4% with a bad category, 5) subject difficulties of 78.2% with a fairly good category, 6) learning material from home by 76% in the fairly good category, 7) learning media from home by 78.7% in the fairly good category, 8) evaluation of learning from home by 75.2% in the fairly good category, and 9) clarity of instructions by 76.6% with quite good category. The results of inferential statistical analysis show that students’ perceptions of learning activities from home affect student learning outcomes in natural science subjects, as evidenced by the correlation coefficient value of 0.272 > 0.05. Future research is expected to be able to dig deeper into other factors that influence student learning outcomes in natural science subjects.